Cave diving for a diagnosis: Disseminated histoplasmosis in the immunocompromised - Mirza, Abu-Sayeef (IDCases, 2018)
Tumor necrosis factor (TNF) inhibitors are widely used in the treatment of inflammatory conditions and are associated with risks of invasive infections. We present a diagnostically challenging patient with unique comorbidities and travel history. A 53-year-old man with a history of polysubstance abuse and psoriasis on adalimumab presented to our hospital directly from the airport with fever, dyspnea, and cough. He had been living in Costa Rica and engaged in many outdoor activities. Within 6 h and a limited history, he was intubated; vasopressors and antimicrobials were promptly administered. An extensive infectious disease investigation was undertaken, considering potential travel-related exposures and his immunosuppressive state. However, multi-organ failure with worsening disseminated intravascular coagulation ensued, and within four days of admission, the patient passed away. Five days after his death, the urine Histoplasma antigen resulted positive. Disseminated histoplasmosis should be suspected in a patient on anti-TNF therapy, with a severe febrile illness and pneumonia refractory to antibacterial therapy. A high index of suspicion is necessary to make the diagnosis and initiate prompt treatment.